Pain sensitivities predict prophylactic treatment outcomes of flunarizine in chronic migraine patients: A prospective study. (August 2022) - Pan, Li-Ling Hope; Wang, Yen-Feng; Ling, Yu-Hsiang; Lai, Kuan-Lin; Chen, Shih-Pin; Chen, Wei-Ta; Treede, Rolf-Detlef; Wang, Shuu-Jiun
Background: We aimed to assess the differences in quantitative sensory testing between chronic migraine and healthy controls and to explore the association between pain sensitivities and outcomes in chronic migraine following preventive treatment. Methods: In this prospective open-label study, preventive-naïve chronic migraine and healthy controls were recruited, and cold, heat, mechanical punctate, and pressure pain thresholds over the dermatomes of first branch of trigeminal nerve and first thoracic nerve were measured by quantitative sensory testing at baseline. Chronic migraines were treated with flunarizine and treatment response was defined as ≥50% reduction in the number of monthly headache days over the 12-week treatment period. Results: Eighty-four chronic migraines and fifty age-and-sex-matched healthy controls were included in the analysis. The chronic migraine had higher cold pain thresholds over the dermatomes of the first branch of trigeminal nerve and the first thoracic nerve ( p  < 0.001 and < 0.001), lower pressure pain thresholds over the dermatomes of the first thoracic nerve ( p  = 0.003), heat pain thresholds over the dermatomes of the first branch of the trigeminal nerve and the first thoracic nerve ( p  < 0.001 and p  = 0.015) than healthy controls. After treatment, 24/84 chronic migraine had treatment response. The responders with relatively normal pain sensitivity had higher heat pain thresholds over the dermatome of the first branch of the trigeminal nerve ( p  = 0.002), mechanical punctate pain thresholds over the dermatomes of the first branch of the trigeminal nerve ( p  = 0.023), and pressure pain thresholds over the dermatomes of the first branch of the trigeminal nerve ( p  = 0.026) than the hypersensitive non-responders. Decision tree analysis showed that patients with mechanical punctate pain threshold over the dermatomes of the first branch of the trigeminal nerve > 158 g ( p  = 0.020) or heat pain threshold over the dermatome of the first branch of the trigeminal nerve > 44.9°C ( p  = 0.002) were more likely to be responders. Conclusions: Chronic migraine were generally more sensitive compared to healthy controls. Preventive treatment with flunarizine should be recommended particularly for chronic migraine who have relatively normal sensitivity to mechanical punctate or heat pain. Trial registration: This study was registered on ClinicalTrials.gov (Identifier: NCT02747940).